Penerapan Model Problem Based Learning Berbantuan Komik dalam Meningkatkan Kemampuan Membaca Pemahaman Siswa di Sekolah Dasar - Hillary Ester Hutasoit; Neneng Sri Wulan; Wina Mustikaati (Lembaga Pengembangan Kinerja Dosen, 2025)
Fifth grade students' consistently poor reading comprehension abilities, which impeded their overall academic development and participation in language acquisition, served as the driving force for this study. Using a comic assisted problem based learning (PBL) model, the study, which involved 39 students at SDN Purwamekar, aimed to improve learning activities in order to increase teacher and student participation and, eventually, improve fifth grade students' reading comprehension skills. By using comic strips to illustrate issues, this creative method made learning more engaging and accessible for younger students. In order to enable iterative improvements, the study was conducted over two cycles using classroom action research technique. Only 25% of students (eight people) successfully completed the learning objectives in the first cycle, according to preliminary findings, while 75% (24 students) failed, suggesting difficulties with student motivation and comprehension. This led to changes like improving comic material and fostering more cooperative conversations. Significant progress was seen by the second cycle, with 30 students meeting the completion criteria and only four falling short of the objectives, indicating improved engagement and skill growth. In conclusion, the comic assisted PBL model effectively boosted reading comprehension skills among fifth grade students. The research underscores the value of integrating visual aids and problem solving in education, offering practical insights for teachers to create more dynamic classrooms. Nonetheless, factors like time constraints and resource availability warrant further exploration to ensure sustainable implementation in diverse educational settings.